A comparison of the opinions of intensive care unit staff and family members of the treatment intensity received by patients admitted to an intensive care unit: A multicentre survey. Issue 5 (September 2019) - Anstey, Matthew H.; Litton, Edward; Jha, Nihar; Trevenen, Michelle L.; Webb, Steve; Mitchell, Imogen A.
Abstract: Background: Achieving shared decision-making in the intensive care unit (ICU) is challenging because of limited patient capacity, leading to a reliance on surrogate decision-makers. Prior research shows that ICU staff members often perceive that patients receive inappropriate or futile treatments while some surrogate decision-makers of patients admitted to the ICU report inadequate communication with physicians. Therefore, understanding the perceptions of both ICU staff and surrogate decision-makers around wishes for ICU treatments is an essential component to improve these situations. Objectives: The objectives of this study were to compare perceptions of ICU staff with surrogate decision-makers about the intensity and appropriateness of treatments received by patients and analyse the causes of any incongruence. Methods: A multicentred, single-day survey of staff and surrogate decision-makers of ICU inpatients was conducted across four Australian ICUs in 2014. Patients were linked to a larger prospective observational study, allowing comparison of patient outcomes. Results: Twelve of 32 patients were identified as having a mismatch between staff and surrogate decision-maker perceptions. For these 12 patients, all 12 surrogate decision-makers believed that the treatment intensity the patient was receiving was of the appropriate intensity and duration. Mismatched patients were more likely to be emergency admissions to ICU compared with nonmismatched patients (0.0% vs 42.1%, p = 0.012) and have longer ICU admissions (7.5 vs 3, p = 0.022). There were no significant differences in perceived communication (p = 0.61). Conclusions: Family members did not share the same perceptions of treatment with ICU staff. This may result from difficulty in prognostication; challenges in conveying poor prognoses to surrogate decision-makers; and the accuracy of surrogate decision-makers.